Comparative study of hydrophobically modified gelatin‐based sealant with commercially available sealants. Issue 4 (5th December 2021) - Mizuno, Yosuke; Watanabe, Shiharu; Katano, Mayumi; Yanagihara, Takahiro; Maki, Naoki; Sato, Yukio; Taguchi, Tetsushi
Abstract: Air leakage is one of the major complications related to pulmonary surgeries. To reduce this complication, we developed a decyl group (C10)‐modified Alaska pollock gelatin (ApGltn) (C10‐ApGltn) sealant and evaluated its practical performance against commercially available sealants, Beriplast® and DuraSeal®. C10‐ApGltn was synthesized by reductive amination of the amino groups in ApGltn with decanal. C10‐ApGltn was crosslinked with a poly(ethylene glycol)‐based crosslinker to form a tissue sealant. The crosslinking time of the C10‐ApGltn sealant was fast enough for curing on tissue and application as a spray system. Although the percent swelling of C10‐ApGltn and DuraSeal was significantly greater than Beriplast, C10‐ApGltn and DuraSeal exhibited excellent tissue sealing properties on pleura tissue under a long‐term moist condition. Additionally, C10‐ApGltn and DuraSeal did not cause severe inflammatory responses in a rat subcutaneous example. Therefore, C10‐ApGltn sealant had comparable tissue sealing properties to DuraSeal under a moist condition, indicating the potential of C10‐ApGltn sealant for pulmonary surgeries.